GE_GERICHTE P/7789/2015 vom 6. Oktober 2016 - GE Cour de justice (2016)
ESCROQUERIE; DOMMAGE; DÉTENTION PROVISOIRE; FRAIS JUDICIAIRES; CONFISCATION(DROIT PÉNAL); PARTIE CIVILE | CP.146; CP.47; CP.51; CPP.122; CO.42.2; CPP.426; CPP.428.3; CP.69; CP.70; CPP.442.4